Factors associated to usual physical activity in women Fatores associados à prática de atividade física habitual em mulheres Factores asociados con la práctica de actividad física habitual en mujeres - de Oliveira P.A.M.* (2015)
© 2015, Redprint Editora Ltda. All rights reserved.Introduction: attention has been focused on investigating the prevalence of physical activity (PA) in different populations. Objective: to analyze factors associated with the usual practice of PA in women from areas of Santa Catarina, Brazil. Methods: the cross-sectional study enrolled a sample of 2750 women with a mean age of 32.97±10.9 years. PA was assessed by the International Physical Activity Questionnaire (IPAQ). The sample was divided into six groups: (Southern Region; Itajaí Valley; Northern Region; Western Region; Highlands Region and the Greater Florianópolis Region, SC, Brazil). Statistical analysis was descriptive and inferential. Results: approximately 68.3% of women were considered sufficiently active (active + very active), in particular the Greater Florianópolis Region, SC, Brazil. In the practice of moderate and moderate + vigorous activity, the women of Western Region presented the highest averages (65±64 min/d; 105±102 min/d), respectively, and those in the range of 20-32 years old showed 61% chance of being considered active compared with women in the range of 46-59 years old. As for the body mass index (BMI), women with normal weight of the South Region and Itajaí Valley regions had 2.24 (95% CI;1.15-4.35) and 1.76 (95% CI; 1.14-2.73) times more chances to be active when compared to the overweight women. Conclusion: women in the regions of Santa Catarina were considered sufficiently active. Moderate + vigorous PA was the most prevalent in the six regions studied.